A(N) (ANARCHE)TYPICAL JOURNEY THROUGH NEW YORK: DON DELILLO’S COSMOPOLIS AS AN AMERICAN POSTMODERN ODYSSEY - BARBU, Maria (Studia Universitatis Babeș-Bolyai Philologia, 2024)
A(n) (Anarche)Typical Journey through New York: Don Delillo’s Cosmopolis as an American Postmodern Odyssey. Journeys made across the North American territories were often made in search of something: a better life, a further frontier space or the lifestyle and the bigger opportunities from the other coast. Other times, mostly towards the second half of the 20th century, these journeys were made out of the sheer pleasure of travelling, having no pre-established routes and allowing themselves to drift endlessly and leave rhizomatic traces on America’s map. In the case of Don DeLillo’s Cosmopolis, these two types of geographical narratives overlap in Eric Packer’s chaotic limousine ride across New York, through which he tries to reach his hairdresser but is forever delayed by various things happening on the streets. Through an in-depth geocritical analysis of why the quintessence of the 21st century’s American space proves to be unnavigable in straightforward and ordered ways anymore, this paper will use Corin Braga’s “anarchetype” to define this type of movement and also to link it to the multiple and decentred identity of the postmodern subject. In addition, the protagonist’s journey through Manhattan will be seen as a postmodern odyssey where the destination eludes the traveller to the point in which the journey’s meaning does not even depend on it anymore. O călătorie (anarhe)tipică prin New York. Odiseea americană postmodernă a lui Don DeLillo în Cosmopolis. Călătoriile prin teritoriile nord-americane au fost deseori făcute în căutare de ceva: o viață mai bună, un spațiu de frontieră mai întins sau stilul de viață și oportunitățile mai mari de pe cealaltă coastă. Alteori, mai ales în a doua jumătate a secolului al XX-lea, aceste călătorii au fost făcute din simpla plăcere de a călători: neavând rute prestabilite, ele lasă urme rizomatice pe harta Americii și se mișcă în derivă de-a lungul acesteia. În cazul romanului Cosmopolis de Don DeLillo, aceste două tipuri de narațiuni geografice se suprapun în plimbările haotice ale lui Eric Packer cu limuzina prin New York, prin care acesta încearcă să ajungă la frizerul său, dar este mereu blocat de diverse lucruri care se întâmplă pe străzi. Printr-o analiză geocritică aprofundată a motivelor pentru care chintesența spațiului american al secolului XXI dovedește imposibilitatea navigării sale în mod direct și ordonat, această lucrare va folosi conceptul de „anarhetip” al lui Corin Braga pentru a defini acest tip de mișcare și, de asemenea, pentru a-l lega de identitatea multiplă și descentrată a subiectului postmodern. În plus, călătoria protagonistului prin Manhattan va fi văzută ca o odisee postmodernă în care destinația își pierde treptat din importanță până la punctul în care sensul călătoriei nu mai depinde deloc de ea. Cuvinte-cheie: Don DeLillo, Cosmopolis, anarhetip, geocriticism, odisee postmodernă, călătorie rizomatică, literatură americană Article history: Received 05 February 2024; Revised 04 April 2024; Accepted 10 April 2024; Available online 25 June 2024; Available print 30 June 2024.